Coarse-grained molecular dynamic simulations of interactions of poly(amidoamine) with sodium octadecyl sulfate at the water/octane interface. (10th January 2020) - Li, Xian; Zhao, Yingying; Gu, Haifeng; Huang, Shuaiyu; Li, Wenzhuo
Abstract: This study investigated the interactions of poly(amidoamine) (PAMAM) and sodium octadecyl sulfate (SOS) molecules at the water/octane interface by analyzing spatial structures and interfacial properties of water/PAMAM/SOS/octane (oil) systems. Coarse-grained molecular dynamic simulations were performed to examine the dependence of the systems on interfacial coverage (IC, corresponding to the concentration of SOS molecules) and PAMAM concentration ( C PAMAM ) in terms of density profiles, interaction energy, interfacial thickness, order parameters ( S CD ), interfacial tension ( γ ), and area compressibility modulus ( K A ). Simulation results showed that the presence of PAMAM molecules had a stronger effect on SOS head groups and pushed the head groups toward the oil phase. The interaction energy between PAMAM and SOS molecules increased with increments of C PAMAM in a fixed IC. Interfacial thickness and S CD increased with increased C PAMAM . The γ value in the presence of PAMAM was lower compared with pure SOS solutions and decreased with increased C PAMAM . The area compressibility modulus ( K A ) of SOS monolayer increased with increased C PAMAM .